Application of EV aggregators and SMES for frequency deviation control using fractional fuzzy controller - Tripathy, Sabita; Debnath, Manoj Kumar; Kar, Sanjeeb Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Secondary controllers are implemented in the alternator control loop to take care of the swinging of frequency initiated due to inequality of load and demand. A fractional fuzzy-PID controller (FFPID) is projected in this work for frequency deviation control in unified system including EV aggregators and superconducting magnetic energy storage (SMES). EVs and SMES are given primacy because of their ecofriendly nature. Proper adjustment of gains of FFPID is also required to extract the best performance of the secondary controllers. Here a recent tuning process named as artificial rabbits optimization (ARO) is applied for proper tuning of projected controller. The implemented dual area power system includes time varying delay-based EV aggregators, SMES, and thermal generating units. The ARO technique is applied in the model to tune the controller constraints with abrupt increment of demand in one of the control areas. A time-based function is treated as fitness function to evaluate the system performance. The dominance property of the projected FFPID controller over conventional PID and FPID controller in terms of different response specifications like maximum positive deviation (overshoot), settling time and minimum negative deviation (undershoot). The robust nature of the projected controller is also confirmed by multiple analysis like random load deviations and system constraint alteration.